Phosphorylation of varicella-zoster virus open reading frame (ORF) 62 regulatory product by viral ORF 47-associated protein kinase. - Ng, T I (1994)
Varicella-zoster virus (VZV) encodes within its unique long region a gene product with protein kinase motifs. In a previous study, we demonstrated that immunoprecipitated VZV open reading frame (ORF) 47 protein was associated with a functional protein kinase activity, on the basis of its ability to both autophosphorylate and phosphorylate artificial substrates. To further define potential substrates of ORF 47-associated protein kinase, we analyzed individual viral phosphoproteins to determine whether any were modified by the viral protein kinase. These candidates included gene products of VZV ORFs 4, 61, 62, and 63, which are homologs of herpes simplex virus type 1 (HSV-1) immediate-early proteins. Each of the above VZV proteins was coimmunoprecipitated with ORF 47 kinase, and the immune complex was incubated in a protein kinase assay. Under these conditions, only the VZV immediate-early ORF 62 protein was phosphorylated by ORF 47-associated protein kinase. The specificity of this phosphorylation event was analyzed by a competition assay in which a recombinant ORF 47 protein lacking enzymatic activity was able to reduce the amount of phosphorylation of ORF 62 protein by VZV ORF 47-associated kinase. To provide an additional evaluation of specificity, the experiment was repeated with [32P]GTP instead of [32P]ATP, because the VZV ORF 47 kinase has the distinctive property of using GTP as a phosphate donor. Again the ORF 62 substrate was phosphorylated. In summary, the VZV ORF 47-associated protein kinase (the HSV-1 UL13 homolog) catalyzed the in vitro phosphorylation of the VZV ORF 62 protein, the homolog of the HSV-1 ICP4 regulatory protein.